Different agglomeration properties of PC61BM and PC71BM in photovoltaic inks – a spin-echo SANS study. Issue 8 (29th January 2020) - Bernardo, Gabriel; Melle-Franco, Manuel; Washington, Adam L.; Dalgliesh, Robert M.; Li, Fankang; Mendes, Adélio; Parnell, Steven R.
Abstract : Fullerene derivatives are used in a wide range of applications including as electron acceptors in solution-processable organic photovoltaics. Abstract : Fullerene derivatives are used in a wide range of applications including as electron acceptors in solution-processable organic photovoltaics. We report agglomeration of fullerene derivatives in optically opaque solutions of PC61 BM and PC71 BM, with concentrations ranging from 30 mg mL −1 up to 90 mg mL −1, in different solvents with relevance to organic photovoltaics, using a novel neutron scattering technique, Spin-Echo Small Angle Neutron Scattering (SESANS). From SESANS, agglomerates with correlation lengths larger than 1 μm are found in some PC61 BM solutions, in contrast no agglomerates are seen in PC71 BM solutions. These results clearly show that PC71 BM is fundamentally more soluble than PC61 BM in the solvents commonly used in photovoltaic inks and corroborating similar observations previously achieved using other experimental techniques. Computer models are presented to study the energetics of solution and agglomeration of both species, ascribing the difference to a kinetic effect probably related to the larger anisotropy of PC71 BM. Also, this work showcases the power of SESANS to probe agglomerates of fullerene derivatives in completely opaque solutions for agglomerates of the order of one to several microns.